Effect of CPAP treatment on endothelial function and plasma CRP levels in patients with sleep apnea - Panoutsopoulos, Athanasios (International Scientific Literature, Inc., 2012)
BACKGROUND: Continuous positive airway pressure (CPAP) is the most effective method for treating obstructive sleep apnea syndrome (OSAS) and alleviating symptoms. Improved sleep quality with effective CPAP therapy might also contribute to attenuated systemic inflammation and improved endothelial function, with subsequent reduction of cardiovascular risk. The aim of this study was to assess the effect of 3-month CPAP therapy on brachial artery flow-mediated dilation (FMD) and plasma C-reactive protein (CRP) levels in patients with OSAS. MATERIAL/METHODS: Our study group consisted of 38 male patients with no prior history of cardiovascular disease. Twenty patients with an Apnea-Hypopnea Index (AHI) ≥15 were assigned to receive CPAP treatment and 18 subjects with an AHI<5 were included in the control group. Six patients failed to comply with the CPAP treatment. Measurement of FMD and blood analysis was performed at baseline and 3 months after CPAP therapy. RESULTS: Baseline FMD values were negatively correlated with age, BMI, AHI, DSI,% of time <90% Sa02, and CRP (p<0.05). Plasma CRP values were positively correlated with BMI, AHI, DSI and% of time <90% Sa02 (p<0.05). In the group of patients who complied with the CPAP treatment, there was a significant increase in the FMD values (9.18±0.55 vs. 6.27±0.50) and a decrease in the levels of CRP (0.67±0.15 vs. 0.84±0.18) (p<0.05). CONCLUSIONS: Appropriate CPAP therapy improved both CRP and FMD values, suggesting its potentially beneficial role in reducing cardiovascular risk in OSAS patients.